TRANSLATION ANALYSIS OF QUESTIONING RESPONSES ON THE NOVEL THE KILL ORDER AND THE TRANSLATION QUALITY - Taufik Nur Hidayat (LinguAmerta, 2024)
This study is about the translation quality on questioning responses in the novel entitled The Kill Order and its translation. This study aimed to describe the function of directive speech act specifically questioning responses and its translation in the novel The Kill Order. Besides it also described the translation techniques used in the translation version. This study used descriptive qualitative by focusing on single case. Data sources used was the novel The Kill Order and its translation. The data of the study was the sentences containing the questioning responses. The results of the study based on 23 data found that there were nine responses of direct speech and two indirect responses. Those functions included asking, commenting, denying, requesting, suggesting, insulting, ridiculing, reviewing, pleading and disagreeing. Whereas for response of indirect speech was no response/answer from the hearer and only face expression. No exists answers and expressions face. The translation technique used in the translation version were six techniques by applying single and couplet techniques. The couplet technique used 23 times while six techniques were single technique. Generally, the technique found in the research were including literal, established equivalence, amplification, reduction, discursive creation, and transposition. While for couplet technique were reduction and addition. The use of those techniques tends to produce the translation quality which less accurate yet they are sill acceptable